2021
DOI: 10.1155/2021/8035997
|View full text |Cite
|
Sign up to set email alerts
|

Wenshen Shengjing Decoction Improves Early Embryo Development by Maintaining Low H3K27me3 Levels in Sperm and Pronuclear Embryos of Spermatogenesis Impaired Mice

Abstract: Many ingredients in Wenshen Shengjing Decoction (WSSJD) can cause epigenetic changes in the development of different types of cells. It is not yet known whether they can cause epigenetic changes in sperms or early embryos. Here, we investigated the role of WSSJD in epigenetic modifications of sperms or early embryos and early embryo development. A mouse model with spermatogenesis disorders was established with cyclophosphamide (CPA). WSSJD was administrated for 30 days. The male model mice after the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The H3K27me3 was detected in the testes of adult porcine, in spermatocytes and round spermatids, but not in elongated spermatids, similar to what was described by An et al [82], who demonstrated the detection of H3K27me3 in spermatogonia, in intermediate spermatocytes, and in round spermatids, and the disappearance of this histone marker on the elongated spermatids. In mice and humans, H3K27me3 is present in mature sperm and is considered an important regulator in sperm development, regulating genes related to meiosis [83,84]. In humans, 12-30% of spermatozoa present heterogeneity in the distribution of H3k9me2, among others such as H3K4Me1, H3K4Me3, H3K79Me2, and H3K36Me3 [85], unlike in newborn or adult porcine, where we did not find this epigenetic marker; however, An et al [82] mention that H3K4me2/3, H3K27me1/2/3, and H4K20me3 are found in the gonocytes of newborn porcine.…”
Section: Epigenetic Markers In Porcine Germ Cellsmentioning
confidence: 99%
“…The H3K27me3 was detected in the testes of adult porcine, in spermatocytes and round spermatids, but not in elongated spermatids, similar to what was described by An et al [82], who demonstrated the detection of H3K27me3 in spermatogonia, in intermediate spermatocytes, and in round spermatids, and the disappearance of this histone marker on the elongated spermatids. In mice and humans, H3K27me3 is present in mature sperm and is considered an important regulator in sperm development, regulating genes related to meiosis [83,84]. In humans, 12-30% of spermatozoa present heterogeneity in the distribution of H3k9me2, among others such as H3K4Me1, H3K4Me3, H3K79Me2, and H3K36Me3 [85], unlike in newborn or adult porcine, where we did not find this epigenetic marker; however, An et al [82] mention that H3K4me2/3, H3K27me1/2/3, and H4K20me3 are found in the gonocytes of newborn porcine.…”
Section: Epigenetic Markers In Porcine Germ Cellsmentioning
confidence: 99%